2022
DOI: 10.1002/fsn3.3119
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping new rapeseed lines based on multiple traits: Application of GT and GYT biplot analyses

Abstract: The selection based on multiple traits enhances the crop cultivars merit to farmers. In this regard, 19 breeding lines as well as two commercial cultivars were studied using a randomized complete block design (RCBD) with three replications in three locations during the 2020–2021 growing season. In this study, to identify the association among different traits and to select the best rapeseed lines based on multiple traits, genotype × trait (GT) and genotype × yield × trait (GYT) biplot analyses were used. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The results of the biplot revealed that most of the studied yield-trait combinations positively correlated with each other mostly because they have the yield component. Similar findings were reported in literature (Karahan & Akgün, 2020;Kendal, 2020;Gholizadeh et al, 2023). Overall, genotypes Turkey and Kenya9819 were ranked as superior because they had aboveaverage yield*trait combinations.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the biplot revealed that most of the studied yield-trait combinations positively correlated with each other mostly because they have the yield component. Similar findings were reported in literature (Karahan & Akgün, 2020;Kendal, 2020;Gholizadeh et al, 2023). Overall, genotypes Turkey and Kenya9819 were ranked as superior because they had aboveaverage yield*trait combinations.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the GYT two‐way table can be displayed in a biplot, referred to as GYT biplot, which allows visualization of the genotypes' overall superiority as well as their trait profiles (strengths and weaknesses) (Yan & Fregeau‐Reid, 2018; Yan et al., 2019). The GYT procedure has already gained some popularity in multi‐trait selection of various crops (e.g., da Cruz et al., 2020; Faheem et al., 2023; Gholizadeh et al., 2023; Karahan & Akgün, 2020; Kendal, 2020; Ma et al., 2023; Merrick et al., 2020; Mohammadi, 2019; Peixoto et al., 2022; Xu et al., 2021). [Correction added on 3 April, after first online publication: missing text “For example … various crops” is added.…”
Section: Introductionmentioning
confidence: 99%
“…GT biplot methodology was used to investigate the interrelationships among different traits of winter oilseed rape genotypes (Dehghani et al., 2008). Recently, new oilseed rape lines were examined based on multiple traits using GT and GYT biplot analysis (Gholizadeh et al., 2022).…”
Section: Introductionmentioning
confidence: 99%